2009
DOI: 10.1080/09638280902822294
|View full text |Cite
|
Sign up to set email alerts
|

What are the experiences of adults returning to work following recovery from Guillain-Barré syndrome? An interpretative phenomenological analysis

Abstract: . What are the experiences of adults returning to work following recovery from Guillain-Barre´ syndrome? An interpretative phenomenological analysis. Disability and Rehabilitation, 31(22): 1817-1827. AbstractPurpose. Guillain-Barre´ syndrome (GBS) is a transient inflammatory disorder affecting peripheral nerves, characterised by weakness and numbness in limbs, upper body and face. Residual problems affect a large minority, and complicate return to work. This qualitative study explored the experiences of people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 27 publications
1
53
0
1
Order By: Relevance
“…The diversity of instruments, as well as the dimensions or variables, used to determine employee well-being after RTW highlights the lack of clarity regarding how this concept should be conceptualized and measured. With regard to design, two studies were qualitative [ 63 , 64 ], the study by Yonezawa et al [ 65 ] can be considered quasi-experimental and the remaining seventeen were correlational. The data were gathered online, by conventional mail or over the telephone (five studies), in person at the workplace (seven studies), or in interviewees’ homes (two studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of instruments, as well as the dimensions or variables, used to determine employee well-being after RTW highlights the lack of clarity regarding how this concept should be conceptualized and measured. With regard to design, two studies were qualitative [ 63 , 64 ], the study by Yonezawa et al [ 65 ] can be considered quasi-experimental and the remaining seventeen were correlational. The data were gathered online, by conventional mail or over the telephone (five studies), in person at the workplace (seven studies), or in interviewees’ homes (two studies).…”
Section: Resultsmentioning
confidence: 99%
“…From a different methodological approach, one the qualitative study [ 64 ] explored the experiences of people who returned to work after being diagnosed with and having recovered from Guillain-Barré syndrome, in order to gain insight into the factors which facilitated or inhibited this process. The interviews revealed that after returning to work, participants continued to experience certain physical and psychosocial difficulties related to the Guillain-Barré syndrome, which required active coping strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have studied involvement, satisfaction, meaning of work, and work engagement, finding that a lack of them is related to sickness absence and not returning to work (53,58,93,94). This is described in a study of return to work after Guillain-Barré disease (95). Value of work is related to the quest for normality, which is often also described in relation to return to work after cancer (8,96,97).…”
Section: Value Of Workmentioning
confidence: 99%
“…5 Joseph H. Friedman, Providence, RI: I applaud the authors of the AMANDYSK trial 1 and agree that their placebo-controlled withdrawal design supports the antidyskinetic effect of amantadine for L-dopa-induced dyskinesias. In addition, the added value of nerve electrophysiology should be investigated to determine the recovery status in GBS.…”
Section: Residual Fatigue In Guillain-barré Syndrome Is Related To Axmentioning
confidence: 99%